Influence of density leaf in calda distribution in canopy coffee (Coffea arabica L.) - Sousa Jr., Jose Marcio; Alves Ruas, Renato Adriane; Duarte, Luiz Otavio; Faria, Vinícius Ribeiro; Carvalho, Alberto; Santos, Carlos Roberto Santos Junior Roberto (Coffee Science - ISSN 1984-3909, 2017)
The inadequacy of the spray volume applied to the target can result in low efficiency and environmental contamination. The objective was to evaluate the influence of canopy characteristics in the distribution of syrup in coffee (Coffea arabica L.). The treatments were applied in a C. cv. “plot Red-144 Catuaí” with average growing volume of 12501 m³ ha-1. The treatments were arranged in sub-scheme of split plots, being three foliar densities (1.0, 1.5 and 2.0 kg m-3 plant-1) constituting the plots, five spray volumes (200; 300; 500, 600 and 800 L ha-1) constituting the subplots and three positions in the coffee canopy (upper Third, middle and lower) constituting the sub-subplots, with four replications. The evaluations were conducted in the months of March, July and December 2015. The variables analyzed were: spray deposition drops density (DD), volume median diameter (VMD) of the droplets and relative amplitude (SPAN) drops spectrum. Density 1.0 kg m-3 plant-1 provided higher spray deposition at densities of 1.5 and 2.0 kg m-3 plant-1 in top positions, middle and lower. In the middle position the leaf density 2.0 kg m-3plant-1 provided DD drops 52 and 44% lower than the 1.0 to 1.5 kg m-3 plant-1, respectively. The average VMD was 184 m and the SPAN 1,3. We conclude that the increase in leaf density provides significant reduction in spray distribution within the canopy of the coffee plants.